2021
DOI: 10.1093/plcell/koab060
|View full text |Cite
|
Sign up to set email alerts
|

The PIF1-miR408-PLANTACYANIN repression cascade regulates light-dependent seed germination

Abstract: Light-dependent seed germination is a vital process for many seed plants. A decisive event in light-induced germination is degradation of the central repressor PHYTOCHROME INTERACTING FACTOR 1 (PIF1). The balance between gibberellic acid (GA) and abscisic acid (ABA) helps to control germination. However, the cellular mechanisms linking PIF1 turnover to hormonal balancing remain elusive. Here, employing far-red light-induced Arabidopsis thaliana seed germination as the experimental system, we identified PLANTAC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 83 publications
1
47
3
Order By: Relevance
“…Second, we showed in the current study that functional GTAC Cu-response motifs are present in the promoters of key ABA biosynthetic genes in phylogenetically representative land plant species (Figure 12 and 13; Supplemental Figure 9 to 11). Additionally, the phenomenon that high Cu increases ABA accumulation has been reported by physiological studies in different plant species (An et al, 2008; Ye et al, 2014; Jiang et al, 2021). Repression of ABA biosynthesis by the SPL7-GTAC circuit thus appears to be a conserved mechanism in land plants.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Second, we showed in the current study that functional GTAC Cu-response motifs are present in the promoters of key ABA biosynthetic genes in phylogenetically representative land plant species (Figure 12 and 13; Supplemental Figure 9 to 11). Additionally, the phenomenon that high Cu increases ABA accumulation has been reported by physiological studies in different plant species (An et al, 2008; Ye et al, 2014; Jiang et al, 2021). Repression of ABA biosynthesis by the SPL7-GTAC circuit thus appears to be a conserved mechanism in land plants.…”
Section: Discussionmentioning
confidence: 76%
“…ABA level in spl7-ko was not further increased by high Cu exposure (Figure 10A). Moreover, we measured ABA content in the wild type and spl7-ko plants at checkpoint III using both the ELISA method and the ultrahigh-performance liquid chromatography-triple quadrupole mass spectrometry (UPLC-MS/MS) method (Fu et al, 2012; Jiang et al, 2021). These analyses confirmed that the amount of ABA was significantly higher in spl7-ko than in the wild type plants (Figure 10B and 10C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to these processes, copper is involved in cell wall lignification and reproduction (Epstein and Bloom, 2005;Broadley et al, 2012;Chen et al, 2020;. Recent studies implicate copper in light-dependent seed germination (Jiang et al, 2020), shaping the shoot architecture, transition to flowering, stigmatic papillae development and senescence (Rahmati . Mounting evidence from studies in animal species also implicates copper in cell signaling through its untraditional role as a modulator of MAPK signaling and mTORdependent autophagic kinase signaling (Turski and Thiele, 2009;Turski et al, 2012;Chang, 2015;Tsang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%